"The Nibelungenlied" and "The Man in the Panther Skin": A Comparison of Two Medieval Epics - Schöffl, Rainer (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2017)
The present paper refers to the most important epics of the High Middle Ages in Germany and Georgia: "The Nibelungenlied" (NL) and "The Man in the Panther Skin" (MPS). Both poems were composed around the year 1200 in very similar social environments (feudal system, court life, chivalry, Christianity), and both were unique secular poetries in those days. A comparison of their characteristics seems therefore appropriate.